Judicial Review of the Determination of the Special Tourism Economic Zones for Project X - Felicia, Felicia (2025, 2025)
Special Economic Zones are economic areas that have special facilities as an effort by the government to attract investors to invest their capital and open up new business opportunities. Reviews related to the implementation of Special Economic Zones must be carried out massively. The implementation of this SEZ must also be accompanied by supervision, both internal and external supervision. Internal supervision can be carried out with inherent supervision, and external supervision can be carried out through the Ombudsman of the Republic of Indonesia. This is an effort to prevent and overcome maladministration in the implementation of public services. The determination of the Special Economic Zone for Tourism Project X does not reflect the appropriate stages which should have begun with a proposal by a business entity or local government. This is also suspected of being a form of maladministration carried out by the government as a public servant because of a conflict of interest which is not a public interest but a form of individual interest. Based on a review with John Rawls' Theory of Justice, the determination of this SEZ does not reflect the concept of justice where there is no equality for everyone who registers their project and follows the SEZ waiting list. This form of SEZ determination is an action that does not guarantee justice and does not consider legal equality for people who do not receive equal treatment and opportunities due to the existence of certain powers or positions for the interests of certain community groups.